Combining Protein Ligation Systems to Expand the Functionality of Semi-Synthetic Outer Membrane Vesicle Nanoparticles - van den Berg van Saparoea, H. Bart; Houben, Diane; Kuijl, Coen; Luirink, Joen; Jong, Wouter S. P. (Frontiers in Microbiology, 2020)
Bacterial outer membrane vesicles (OMVs) attract increasing interest as immunostimulatory nanoparticles for the development of vaccines and therapeutic agents. We previously engineered the Escherichia coli virulence factor Hemoglobin protease (Hbp) into a surface display vector that can be expressed to high density on bacterial cells and derived OMVs. Moreover, we reported about the use of Tag-Catcher protein ligation technology in combination with the Hbp platform, to obtain dense display of heterologous antigens and nanobodies on the surface of Salmonella OMVs. Here we show that this system can be expanded, by coupling proteins via the Spy system to internal domains of the Hbp stem structure. Inserted SpyTags were shown to be accessible and to efficiently couple SpyCatcher fusion proteins. Next, we combined N-terminal SnoopCatcher or SnoopTag sequences with internal SpyTags in a single Hbp molecule. This allowed coupling of two proteins to a single Hbp carrier molecule without obvious steric hindrance effects. Since coupling occurs after translocation of the Hbp across the bacterial outer membrane, there are no limitations to the size and complexity of the partner proteins. In conclusion, we constructed a versatile modular platform for the development of bivalent recombinant OMV-based vaccines and therapeutics.